Contrast-Enhanced CT May Be a Diagnostic Alternative for Gastroesophageal Varices in Cirrhosis with and without Previous Endoscopic Variceal Therapy - Li, Qianqian (Gastroenterol Res Pract, 2019)
BACKGROUND AND AIMS: Liver fibrosis blood tests, platelet count/spleen diameter ratio (PSR), and contrast-enhanced CT are diagnostic alternatives for gastroesophageal varices, but they have heterogeneous diagnostic performance among different study populations. Our study is aimed at evaluating their diagnostic accuracy for esophageal varices (EVs) and gastric varices (GVs) in cirrhotic patients with and without previous endoscopic variceal therapy. METHODS: Patients with liver cirrhosis who underwent blood tests and contrast-enhanced CT scans as well as endoscopic surveillance should be potentially eligible. EVs needing treatment (EVNTs) and GVs needing treatment (GVNTs) were recorded according to the endoscopic results. Area under the curves (AUCs) were calculated. RESULTS: Overall, 279 patients were included. In 175 patients without previous endoscopic variceal therapy, including primary prophylaxis population (n = 70), acute bleeding population (n = 38), and previous bleeding population (n = 67), the diagnostic accuracy of contrast-enhanced CT for EVNTs was higher (AUCs = 0.816‐0.876) as compared to blood tests and PSR; by comparison, the diagnostic accuracy of contrast-enhanced CT for GVNTs was statistically significant among primary prophylaxis population (AUC = 0.731, P = 0.0316), but not acute or previous bleeding population. In 104 patients with previous endoscopic variceal therapy (i.e., secondary prophylaxis population), contrast-enhanced CT was the only statistically significant alternative for diagnosing EVNTs and GVNTs but with modest accuracy (AUCs = 0.673 and 0.661, respectively). CONCLUSIONS: Contrast-enhanced CT might be a diagnostic alternative for EVNTs in cirrhotic patients, but its diagnostic performance was slightly weakened in secondary prophylaxis population. Additionally, contrast-enhanced CT may be considered for diagnosis of GVNTs in primary prophylaxis population without previous endoscopic variceal therapy and secondary prophylaxis population.